Cooling in a low-resource environment: Lost in translation. Issue 2 (April 2015) - Montaldo, Paolo; Pauliah, Shreela S.; Lally, Peter J.; Olson, Linus; Thayyil, Sudhin
Summary: Although cooling therapy has been the standard of care for neonatal encephalopathy (NE) in high-income countries for more than half a decade, it is still not widely used in low- and middle-income countries (LMIC), which bear 99% of the encephalopathy burden; neither is it listed as a priority research area in global health. Here we explore the major roadblocks that prevent the use of cooling in LMIC, including differences in population comorbidities, suboptimal intensive care, and the lack of affordable servo-controlled cooling devices. The emerging data from LMIC suggest that the incidence of coexisting perinatal infections in NE is no different to that in high-income countries, and that cooling can be effectively provided without tertiary intensive care and ventilatory support; however, the data on safety and efficacy of cooling are limited. Without adequately powered clinical trials, the creeping and uncertain introduction of cooling therapy in LMIC will be plagued by residual safety concerns, and any therapeutic benefit will be even more difficult to translate into widespread clinical use.